Práticas de cuidado com o uso de insulina por usuários com diabetes mellitus tipo 2 - Silva, Adrielle Chermont da (2017)
The goals of this study were to get acquainted with the health care practices with the usage of insulin by users diagnosed with Diabetes Mellitus, Type 2 at their residences; to implement, during the home visit, health education actions to insulin dependent Diabetes Mellitus, Type 2 diagnosed users; to discuss the repercussion of the health education actions on insulin dependent users with Diabetes Mellitus, Type 2 on the domiciliary context. It is about a qualitative field research based on Converging Assistance Research metodological proposal. In order of having a triangulation of the data, a documental analysis on the users’ medical records was done, followed by participant observation and a semi structured interview. This study was made at the residences of users diagnosed with Diabetes Mellitus, Type 2, having as inclusion criteria being insulin dependent and realizing its self-appliance. The data collection was conducted between April and August of 2016. The ethical aspects of research in humans were respected, acording to National Health Council (CNS) Resolucion 466/12. The study was analyzed in accordance with the proposal of Converging Assistance Research. Nine users were a part of this research, seven being women and two men. The age ranged from 50 to 69 years of age. Two weren’t literate and the maximum time of study was 8 years. The users saw the Diabetes as a “bad” disease, because it generates health complications, and the usage of insulin was tolerated given that it’s needed to use it to be fine. Many of the observed practices were done incorrectly, such as the non-monitoring of glycaemia, storage site, asepsis on the flask before aspiring it, aspiring of the prescribed dosage, rotation on the places of appliance, reutilization and disposal of sharp material. The lack of information about such practice can be observed, being the Community Health Workers the closer professional to the users, also as being the one who realizes health education activities during his or her domiciliary visits. When consulting the medical records, it wasn’t foud, exactly, which orientations were realized. The doctor is the professional who registers the most orientations and the nurse, rarely. Besides realizing the procedure along with the participant, orientations were realized according to each participant’s needs. The adopted method allowed the realization of health education actions during the whole data collection, fact that helped in the modification of incorrect methods that were being adopted. Including the users in the decision making process humanizes and qualifies the service. The creation of a more efficient public policy for the monitoring of the self-usage of insulin is made necessary.